Analisis Kemampuan Literasi Membaca Siswa Kelas V dari Perspektif Guru Kelas V SD - Agustinus Edi Prasetya; Galih Kusumo (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Fifth grade elementary school teachers are able to determine their students' reading literacy abilities. The aim of the research is to narrate the fifth grade reading literacy skills from the perspective of the fifth grade elementary school teacher. The research method used is descriptive qualitative research. The data collection technique used was interviews. The data analysis technique applied is descriptive qualitative data analysis to discuss research results and determine conclusions. There were 26 fifth grade students who were the subjects of the research. The research results showed that fifth grade students had good reading literacy skills in understanding various fiction and non-fiction texts, although there were three students with special needs who were still having difficulties. There are 26 out of 26 students who regularly borrow and read various books in the library every Friday. Morning literacy and literacy activities every Friday after gymnastics make students' literacy skills better. There were also 23 out of 26 students who were able to understand the content of reading fairy tales, short stories, explanatory texts, math story problems and thematic lesson material. This research can be applied for consideration by teachers in improving the reading literacy skills of fifth grade students.